Officer involved domestic violence: A future of uniform response and transparency. (June 2018) - Russell, Brenda L; Pappas, Nicholas
Very little is known about officer-involved domestic violence (OIDV). Although the International Association for Chiefs of Police has developed model policies about OIDV, the extent to which agencies adopted these policies across the United States remains unclear. Similarly, research on and attention to OIDV have diminished substantially since the 1990s. Officer training on OIDV is also rare, but pilot studies examining the use of new curriculum show promise. Yet, there is so much more to be done. This article reviews research and policy on OIDV and seeks to provide motivation for uniformity of policy implementation and officer response to OIDV, calling for transparency via research and reporting.